PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT BERBANTUAN MIND MAPPING PADA PEMBELAJARAN SEJARAH DI KELAS XI F6 SMA N 1 BATIPUH - Puja Mardhatillah; Liza Husnita; Kaksim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low academic performance of 11th grade students at SMA Negeri 1 Batipuh, particularly those in class XI F6, whose average scores were still below the minimum passing grade of 80. The problems identified were the lack of variety in the teaching models used by teachers and the minimal interaction among students, resulting in a lack of in-depth understanding of historical material. The objective of this study is to describe the implementation of the Cooperative Script learning model assisted by Mind Mapping to enhance student activity and understanding in history learning. The research method used is descriptive qualitative, employing data collection techniques such as observation, interviews, documentation, and triangulation. The research subjects are students in class XI F6 during the second semester of the 2024/2025 academic year. Data analysis was conducted inductively through data reduction, data presentation, and conclusion drawing. The research results indicate that the application of Cooperative Script assisted by Mind Mapping can create a more active, interactive, and focused learning environment. Students become more confident in expressing their opinions, more active in discussions, and find it easier to understand the material through mind mapping visualization. The challenge encountered is that some students remain passive; however, overall, this model is effective in improving students' understanding of the material, memory retention, and communication skills compared to the lecture method.